Correlation Between Students' Reading Interest at Home and Summary Writing Ability: A Study of Fifth-Grade Students - Asni, Nasution; Sutikno; Rahmat Kartolo (International Journal of Educational Research Excellence, 2026)
This study investigates the correlation between students' reading interest at home and their summary writing ability among fifth-grade students at UPT SD Negeri 060819 Medan during the 2025-2026 academic year. The research employed a quantitative correlational design with 25 fifth-grade students as participants. Data were collected through a reading interest questionnaire and a summary writing test. Results from normality testing indicated that data were normally distributed (significance value = 0.086 > 0.05), confirming the appropriateness of parametric statistical analysis. The Pearson Product Moment correlation analysis yielded a correlation coefficient of 0.811, which exceeded the critical value of 0.396 at a 5% significance level (N = 25), leading to acceptance of the alternative hypothesis. The coefficient of determination (R² = 65.77%) indicates that approximately 66% of the variance in summary writing ability can be explained by reading interest at home. Based on interpretation guidelines, this correlation coefficient of 0.811 represents a very strong positive relationship. These findings demonstrate that students with higher reading interest at home demonstrate correspondingly better summary writing abilities. The study concludes that fostering reading interest among students, both in family and school environments, should be prioritized to enhance literacy skills, particularly in written expression and comprehension